Trade Impacts of South Asian Free Trade Agreements in Sri Lanka. Issue 1 (March 2019) - Taguchi, Hiroyuki; Rubasinghe, Don Chalani Imasha
This article aims to examine the trade effects of the South Asian Free Trade Agreement (SAFTA) with a focus on Sri Lanka, by applying a gravity trade model. The study targets the following three FTAs: the SAFTA, the India–Sri Lanka Free Trade Agreement (ISFTA), and the Pakistan–Sri Lanka Free Trade Agreement (PSFTA). The outcomes of the gravity trade model estimation suggested that the trade creation effects were identified in the ISFTA, while those were not verified in the SAFTA and that the PSFTA had the trade creation effects only on the Sri Lankan imports. Those results seem to reflect the differentials in the preferential tariff rates. In particular, ISFTA could have the predominant positive effects on Sri Lankan trade flows due to its lowest preferential tariff rates, and thus the SAFTA effect might be crowded out at the current stage of Sri Lankan trade. JEL: F13, F14, O53